Pelatihan dan Pendampingan Arsip Digital Menggunakan Codeigniter di MAS Darrul Mukarram Barito Kuala - Trianiza, Ice; Sidiq, Abdurahim; Muttaqin, Idzani; Muammar, Rais; Hidayati, Tazkia Nor; Akhmad, Rizky Yanuar; Fitriyani, Nanda (Yayasan Sagita Akademia Maju, 2025)
In the digital era, technological transformation was very important to support the smoothness and efficiency of data and information management. At the level of educational and religious institutions such as Mas Darrul Mukarram Barito Kuala, the existence of archives and documentation was essential, both for internal administrative needs and for public services. However, conventional archive management was still mostly done manually, which was prone to damage and data loss. In addition, the unstructured data search process made archive management efficiency very low. Therefore, the implementation of a digital archiving system became the right solution. By using appropriate technology such as CodeIgniter, which was a lightweight and efficient PHP framework, archive management became easier, faster, and more secure.